Plasma paraoxonase activity and oxidative stress and their relationship to disease severity in children with allergic rhinitis - Ozkaya, Emin; Akduman, Hasan; Erenberk, Ufuk; ERENBERK, UFUK; Demir, Aysegul; Dundaroz, M. Rusen (My University, 2013)
Background: Oxidative stress may play a role in the pathophysiology of several diseases including allergic rhinitis (AR). In children with AR an antioxidant enzyme paraoxonase (PON1) has not been previously investigated. The aim of this study was to investigate plasma PON1 activity and plasma total oxidant status (TOS), which are in the form of plasma reactive oxidants, and their association with severity of disease in house-mite-sensitive children with AR.